2013
DOI: 10.1002/stem.1489
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of human embryonic stem cell-derived NKX6.1-expressing pancreatic progenitor cells accelerates the maturation of insulin-secreting cells in vivo

Abstract: Human embryonic stem cells (hESCs) are considered a potential alternative to cadaveric islets as a source of transplantable cells for treating patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
234
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(247 citation statements)
references
References 36 publications
13
234
0
Order By: Relevance
“…After the 14-day differentiation in vitro, hESC-derived cells were ;99.5% PDX1 + and 70% NKX6.1 + before transplant ( Supplementary Fig. 1), consistent with previous studies (5)(6)(7)13). The progenitor population also contained ;14% endocrine cells, which coexpressed NKX2.2, but were largely NKX6.1 2 ( Supplementary Fig.…”
Section: Thyroid Hormone Deficiency Hinders the Development Of Hesc-dsupporting
confidence: 88%
“…After the 14-day differentiation in vitro, hESC-derived cells were ;99.5% PDX1 + and 70% NKX6.1 + before transplant ( Supplementary Fig. 1), consistent with previous studies (5)(6)(7)13). The progenitor population also contained ;14% endocrine cells, which coexpressed NKX2.2, but were largely NKX6.1 2 ( Supplementary Fig.…”
Section: Thyroid Hormone Deficiency Hinders the Development Of Hesc-dsupporting
confidence: 88%
“…Their abundance appeared to decline progressively from the onset of endocrine differentiation at 8 wpc and they were barely detected in adult pancreas. Although the dual-stained cells expressed the α-cell transcription factor ARX, they lacked β-cell ones, PDX1, NKX6.1 and MAFA, consistent with the in vitro PSC-derived bihormonal cells, which seem capable of forming monohormonal glucagonpositive cells upon transplantation (Kelly et al, 2011;Rezania et al, 2013). However, coupled with data from mouse, there is no evidence that the native bihormonal cells are the natural forerunner of any mature type of endocrine cell and, indeed, data imply the contrary (Herrera, 2000).…”
Section: Mapping Human Psc Differentiation Onto Human Pancreas Develosupporting
confidence: 71%
“…This was also the case for subcutaneous implants in a TheraCyte macroencapsulation device (TheraCyte Laguna Hills, CA), but with low plasma huC-peptide levels and poor glucose responsiveness (2). Later studies showed formation of glucose-responsive ␤-cells when only the NKX6.1-enriched fraction was implanted (31). The appearance of plasma huCpeptide levels, increasing after glucose injection with a decrease in glycemia, is in itself insufficient evidence for formation of metabolically adequate ␤-cells, a requirement to qualify for ␤-cell replacement.…”
mentioning
confidence: 89%